FACTORS RELATED TO THE INCIDENT OF DIAPER RASH IN BABIES AT POSYANDU MELATI SUCI 3-4 SUKAKARYA DISTRICT, BEKASI DISTRICT, 2023 - Khodijah, Khodijah; Fatdo Wardani, Ika Kania (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
(WHO) in 2012, the prevalence of skin irritation (diaper rash) in babies aged 0-12 months is quite high, 25% of the 6,840,507,000 babies born in the world, most of whom suffer from diaper rash due to the use of diapers . WHO literature estimates in 2020 regarding diaper rash rates vary widely, ranging from 16% to 65%, and considering the short duration of diaper rash (usually 2-4 days). The aim of this research is to determine the relationship between age, education, employment, knowledge and the role of parents with the incidence of diaper rash in babies at Posyandu Melati Suci 3-4 Sukakarya District, Bekasi Regency in 2023 The research method used is a cross sectional survey method. The analysis used is the Chi Square Test. This research uses primary data from interviews and filling out questionnaires by respondents. The results of the research show that the variables associated with diaper rash in babies at Posyandu Melati Suci 3-4, Sukakarya District, Bekasi Regency in 2023 are maternal education (p value 0.014), maternal knowledge (P value 0.029), while factors that are not related are age (P value 0.728), work (P value 1.000), parental role (P value 0.494). Advice to health workers to provide education on how to maintain the cleanliness of the baby's anogenital area by avoiding the use of disposable diapers in order to reduce the number of skin disorders in babies and toddlers